2015
DOI: 10.7763/ijcea.2015.v6.447
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Agitation Speed for Enzymatic Hydrolysis of Tapioca Slurry Using Encapsulated Enzymes in an Enzyme Bioreactor

Abstract: Abstract-Agitation speed is an important factor in the industrial application for the mixing efficiency in order to increase productivity. In this study, the effect of agitation speed was investigated in a stirred bioreactor for hydrolysis of tapioca slurry into glucose by using encapsulated enzymes within calcium alginate-clay (alg-clay) beads. The hydrolysis process was tested at various agitation speeds from 40 to 200 rpm. The stability of alg-clay beads was examined in term of morphology of beads, enzyme l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In another study, 150 rpm of agitation gave the highest yield of reducing sugar from POME [28] and PKC [18]. The agitation speed is an important parameter for mixing efficiency to raise productivity [30]. Purwanto et al [29] reported that the lower and higher speed decreased the productivity of the enzymatic hydrolysis process due to the sensitivity of the enzyme to mechanical shear stress.…”
Section: Effect Of Agitationmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, 150 rpm of agitation gave the highest yield of reducing sugar from POME [28] and PKC [18]. The agitation speed is an important parameter for mixing efficiency to raise productivity [30]. Purwanto et al [29] reported that the lower and higher speed decreased the productivity of the enzymatic hydrolysis process due to the sensitivity of the enzyme to mechanical shear stress.…”
Section: Effect Of Agitationmentioning
confidence: 99%
“…The interface of the parameters, those that were narrowed down through PBD, is optimized considering the quadratic, interaction, and linear effects in the treatment under CCD. Several researchers have utilized these optimization methods to evaluate the maximum production of reducing sugar [30]. From the OFAT studies, the significant factors were imperiled to an optimization process in the form of FCCCD under the RSM method to obtain the optimum enzymatic hydrolysis conditions for maximal reducing sugar yield.…”
Section: Effect Of Phmentioning
confidence: 99%
“…The mixing efficiency plays an important role in the optimization process of a bioreactor because enzymes are sensitive to mechanical shear stress. Therefore, excessive and lower agitation speed can reduce the efficiency of hydrolysis process (Abd Rahim, Sulaiman, Hamid, Edama, & Baharuddin, 2015). Agitation intensity of the culture broth has multiple effects on microorganisms, such as rupturing of the cell wall, alteration in the fungal morphology, fluctuation in the growth rate and efficiency which in turns affect the rate of desire product formation (Purwanto, Ibrahim, & Sudrajat, 2009).…”
Section: Optimization Of Different Factors For Enhanced Production Of...mentioning
confidence: 99%
“…Effect of reaction time on the production of CD using CGTase from Bacillus licheniformis was conducted at various reaction times of 1, 2, 3, 4 and 5 hr (Rahim et al 2015). About 20 ml of soluble potato starch solution with concentration of 6% (w/v) was prepared in 50 mM sodium phosphate buffer (pH 6.0) by gelatinize in a steam water bath for 10 min and the solution was allowed to cool at room temperature.…”
Section: Reaction Timementioning
confidence: 99%